Functional Analysis of Pepper F-box Protein CaDIF1 and Its Interacting Partner CaDIS1: Modulation of ABA Signaling and Drought Stress Response - Lim, Junsub; Lim, Chae Woo; Lee, Sung Chul (Frontiers in Plant Science, 2019)
Plant adaptive responses to environmental stress are coordinated by inhibition of plant growth and development. Abscisic acid (ABA) is a major phytohormone that regulates the stress response, and its sensitivity determines stress tolerance levels. In this study, we report the identification and functional role of a novel F-box protein, CaDIF1 (Capsicum annuum Drought-Induced F-box Protein 1). The expression of CaDIF1 in pepper leaves was induced by ABA, drought, H2O2, and NaCl treatments. In comparison with wild-type pepper plants, CaDIF1-silenced pepper plants exhibited a drought-sensitive phenotype, whereas CaDIF1-overexpressing (OX) plants exhibited ABA-sensitive and drought-tolerant phenotypes. Using a yeast 2-hybrid assay, we identified CaDIS1 (Capsicum annuum DIF1-Interacting SKP 1), which interacts with CaDIF1 in the cytoplasm and nucleus. Consistent with CaDIF1-silenced pepper plants, CaDIS1-silenced pepper plants displayed ABA insensitivity and reduced drought tolerance, and these were characterized by larger stomatal apertures and greater transpirational water loss. Taken together, our results indicate that CaDIF1 and its interacting partner CaDIS1 synergistically regulate the ABA-dependent defence signalling response to drought stress.